Improving The Efficiency and Quality of Sharia General Insurance at Sun Life Insurance at PT. Sun Life Syariah Medan Branch - Nurjannah Nurjannah; Rahmi Syahriza (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In general, insurance is providing risk protection to the insurer, namely an insurance organization and an agreement agreed upon for a certain period of time. PT Sun Life Syariah Medan Branch is a Sharia general insurance organization located on Jl. Captain Jumhana No. 127, Sukaramai II, Kec. Medan Area, Medan City, North Sumatra. The aim of this research is to find out how to increase the efficiency and quality of superior Sharia general insurance products at PT Sun Life Syariah Medan Branch. The research method uses qualitative methods. The research results obtained are that the level of efficiency of an organization is not determined by the amount of total income, total expenditure, or the total capital owned by the company. However, on the contrary, it is influenced by the business's ability to maximize profits through the effective use of its own resources, which determines the level of efficiency. For this reason, it can be concluded that the Sun Life Financial Syariah Medan Branch organization has better management skills than traditional insurance organizations to design products optimally and minimize the costs required.